Assessment of biological and agronomic diversity of seven durum wheat varieties cultivated in the Northeastern region of Algeria (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Boudersa N, Chaib G, Atoui A, Cherfia R, Bouderbane H, Boudour L. 2021. Assessment of biological and agronomic diversity of seven durum wheat varieties cultivated in the Northeastern region of Algeria. Biodiversitas 22: 1025-1036. The present work was carried out during the 2017/2018 agricultural season, at the experimental station of the ‘Institut Technique des Grandes Cultures’ (ITGC) – El Khroub, Constantine, Algeria. The main objective of this study was the evaluation and the characterization of seven varieties of durum wheat (Triticum durum Desf.) in terms of their behavior and yield. For these reasons, several phenological, morpho-physiological, and biochemical traits, as well as the yield with its components were studied. The obtained results showed a significant variety effect, in particular, for the variables corresponding to the production and to the tolerance. The analysis of the correlation coefficients indicated that the number of spikes per m2, the number of grains spike-1, and the rate of chlorophyll pigments in the leaves were the most related characteristics to grain yield. Indirect selection for breeding productivity through these traits could prove to be effective. Besides, it revealed that tall varieties displayed better resistance to possible hazards; had high relative water content (RWC), accumulated more soluble sugars and proline, as well as, they showed a low level of Malondialdehyde (MDA) compared to other varieties. In addition, this study allowed us to determine many relationships between the studied parameters, that can make a contribution in both the productivity and the adaptation improvement programs of the durum wheat.